Il Bestiario di Arturo Loria: un doppio debutto mancato - Marchi, Monica (L'ospite ingrato, 2025)
The essay analyzes the initial stage of the complex publication history of Il Bestiario by Arturo Loria, a slender volume of 39 poems that came to light only after the author’s death in 1957, thanks to the efforts of his friend Alessandro Bonsanti. The book – as revealed by unpublished correspondence (held at the Archivio Contemporaneo «Alessandro Bonsanti» in Florence and at the Archivio Casa editrice Neri Pozza in Vicenza) – was originally intended to inaugurate the «Poesia» series by Neri Pozza, a close friend and affectionate supporter of the poet-novelist, for whom Loria also carried out significant advisory and mediation work. After examining the very few reviews that accompanied the book’s release, the essay retraces the key moments in the relationship between Loria and Pozza, from their first encounter to the eventual launch of the «Poesia» series with La gaia gioventù by Antonio Barolini.